Determination of the Oswestry Disability Index score equivalent to a "satisfactory symptom state" in patients undergoing surgery for degenerative disorders of the lumbar spine-a Spine Tango registry-based study - Van Hooff, M; Mannion, A; Staub, L; Ostelo, R; Fairbank, J (Elsevier, 2016)
Background Context The achievement of a given change score on a valid outcome instrument is commonly used to indicate whether a clinically relevant change has occurred after spine surgery. However, the achievement of such a change score can be dependent on baseline values and does not necessarily indicate whether the patient is satisfied with the current state. The achievement of an absolute score equivalent to a patient acceptable symptom state (PASS) may be a more stringent measure to indicate treatment success. Purpose This study aimed to estimate the score on the Oswestry Disability Index (ODI, version 2.1a; 0–100) corresponding to a PASS in patients who had undergone surgery for degenerative disorders of the lumbar spine. Study Design/Setting This is a cross-sectional study of diagnostic accuracy using followup data from an international spine surgery registry. Patient Sample The sample includes 1,288 patients with degenerative lumbar spine disorders who had undergone elective spine surgery, registered in the EUROSPINE Spine Tango Spine Surgery Registry. Outcome Measures The main outcome measure was the ODI (version 2.1a). Methods Surgical data and data from the ODI and Core Outcome Measures Index (COMI) were included to determine the ODI threshold equivalent to PASS at 1 year (±1.5 months; n=780) and 2 years (±2 months; n=508) postoperatively. The symptom-specific well-being item of the COMI was used as the external criterion in the receiver operating characteristic (ROC) analysis to determine the ODI threshold equivalent to PASS. Separate sensitivity analyses were performed based on the different definitions of an “acceptable state” and for subgroups of patients. JF is a copyright holder of the ODI. Results The ODI threshold for PASS was 22, irrespective of the time of follow-up (area under the curve [AUC]: 0.89 [sensitivity Se: 78.3%, specificity Sp: 82.1%] and AUC: 0.91 [Se: 80.7%, Sp: 85.6] for the 1- and 2-year follow-ups, respectively). Sensitivity analyses showed that the absolute ODI-22 threshold for the two follow-up time-points were robust. A stricter definition of PASS resulted in lower ODI thresholds, varying from 16 (AUC=0.89; Se: 80.2%, Sp: 82.0%) to 18 (AUC=0.90; Se: 82.4%, Sp: 80.4%) depending on the time of follow-up. Conclusions An ODI score ≤22 indicates the achievement of an acceptable symptom state and can hence be used as a criterion of treatment success alongside the commonly used change score measures. At the individual level, the threshold could be used to indicate whether or not a patient with a lumbar spine disorder is a “responder” after elective surgery.